Exploring the needs of the family caregiver of persons with spinal cord injury: An integrative review - Carla Sílvia Fernandes; Cheila Pessoa; Paula Nogueira (Tehran University of Medical Sciences, 2022)
Background & Aim: A spinal cord injury is a critical event that results in significant life changes for the injured person and the family and caregiver. This study aimed to identify and describe the primary needs of family members that are caregivers of patients with spinal cord injuries. Methods & Materials: An integrative review study was conducted. The studies were collected from five databases, with no time limit until December 2021: MEDLINE® (Medical Literature Analysis and Retrieval System Online), CINAHL® (Cumulative Index to Nursing and Allied Health Literature), Psychology and Behavioural Sciences Collection, SCOPUS, SciELO (Scientific Electronic Library Online). The inclusion criteria for the accessed literature were: adults over 18 years of age who are caregivers of individuals with spinal cord injury; encompassing all the existing needs experienced by caregivers; including care recipients over 18 years old and who spinal cord injury patients are; and primary studies published without time limit. We performed a synthesis of the contents with an a priori categorization. Results: The search resulted in 1018 bibliographic records. A total of 17 articles published between 1981 and 2020 that met the inclusion criteria were selected. The priority categorization process resulted from the study by Fernandes and Angelo in the following five thematic areas: the transition to care, being responsible for everything, the importance of support, access to formal support, communication, and information processes. Conclusion: Family caregivers are important to support people with spinal cord injury, and they present numerous needs that should be the target of intervention by nurses at all stages of rehabilitation.